Short-term earnings mobility in the Canadian and German context: the role of cognitive skills - Ashley Pullman; Britta Gauly; Clemens Lechner (Journal for Labour Market Research, 2021)
It is well-established that human capital contributes to unequal levels of earnings mobility. Individuals with higher levels of human capital, typically measured through education, earn more on average and are privy to greater levels of upward change over time. Nevertheless, other factors may have an incremental effect over education, namely cognitive ability and the skill demands of employment. To deepen insight into whether these aspects contribute to earnings mobility over a four-year period, the present study examines positional change in Canada and Germany-two contexts typified as examples of liberal and coordinated market economies. A series of descriptive indices and relative change models assess how different measures of human capital are associated with earnings mobility. The results indicate that, while individuals with higher cognitive skills experience greater earnings stability and upward mobility in both countries, there is only an incremental effect of skills on mobility in Germany once we account for educational credentials. The results also provide evidence on the role of skill demands for earnings mobility; in both countries, advanced skills at work are associated with greater short-term mobility, even while controlling for cognitive ability and other factors. Together the results showcase how longitudinal data containing detailed measures of human capital allow for deeper insight into what facilitates earnings mobility.
Keywords: I24; I26; J24; J31; 330; Earnings mobility; Human capital; PIAAC; Relative income position; Cognitive skills